PENGARUH INOVASI DAN KREATIFITAS TERHADAP SIKAP KERJA DAN KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KUBU RAYA - B2042142005, ISHAK (Equator Journal of Management and Entrepreneurship (EJME), 2017)
The purpose of this study was to examine and analyze the impact of innovation and creativity of the work attitude and its impact on the performance of staff at the Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya. Forms of this research using descriptive causal comparative. Collecting data using primary data in the form of questionnaires and interviews and secondary data sourced from the Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya. Sample using a sample census. The sample in this study is overall employee at the Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya as many as 62 people. The results of this study indicate that 1. The test results showed that the variables of innovation influence the work attitude. The test results showed that the variables of creativity does not affect the work attitude. The test results showed that the variables of innovation influence on employee performance. The test results show that creativity variables affect the performance of employees. The test results that work attitude variables affect the performance of employees and can be empirically proven. Keywords: Innovation, Creativity, Work Attitude and Performance Officer.